Modelling of a shape memory control system and L2 stability analysis - Abdul Wahab, Norhaliza (Universiti Teknologi Malaysia, 2004)
Simple, light, and powerful, shape memory actuators hold much promise for the future of development technology of engineering. Since the discovery of shape memory in nickel-titanium, a number of inventions have been made having applications in medicine, aerospace, automotive, and consumer products. In this thesis, a discussions about the application of shape memory alloys (SMA) and shape memory effect to actuators will be explained more detail and specified. Conventional actuators also elaborated for gives early approach to understanding the operations of actuator in engineering. A simple shape memory alloy-actuated position control system was developed by an experimental system using a single SMA wire actuator, under constant load. The dissipativity-related stability was applied to an experimental. It is shown that, for a broad class of di-ssipativity controllers, the system will be L2 stable for some range of non-zero loop gain. This applies to the common P, PI, PD, and PID controllers, among others, and believe to be the first result of its kind. During the experimental, three different parameters have been achieved and simulation result will be shows for approach of stability system. It is shown that, interesting non-linear dynamic characteristics of the SMA actuator.